2009
DOI: 10.3109/09513590903056134
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone addition to estrogen therapy – Effects on inflammatory markers for cardiovascular disease

Abstract: Data suggest that testosterone addition to estrogen treatment in postmenopausal women has a modest influence on inflammatory markers and there were no apparent adverse effects. On the contrary, the estrogen-induced increase in hsCRP was suppressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Four studies were double-blind randomized controlled trials, 2 were randomized controlled trials, and 1 was observational. Of the 7 studies included in the data extraction, 4 reported improvements in cardiovascular risk markers, which included improvements in functional capacity [ 12 ], ventilatory efficiency [ 12 ], muscle strength [ 12-14 ], cholesterol [ 13 , 15 , 16 ], inflammatory markers [ 16 , 17 ], and lean body mass [ 13 , 14 , 16 , 18 ]. Conversely, 4 of the 7 studies reported negative effects on high-density lipoprotein (HDL) cholesterol [ 14 , 15 , 17 ], visceral adipose tissue (VAT) [ 15 ], increased insulin resistance, and increased risk of cardiovascular disease (CVD) [ 12 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies were double-blind randomized controlled trials, 2 were randomized controlled trials, and 1 was observational. Of the 7 studies included in the data extraction, 4 reported improvements in cardiovascular risk markers, which included improvements in functional capacity [ 12 ], ventilatory efficiency [ 12 ], muscle strength [ 12-14 ], cholesterol [ 13 , 15 , 16 ], inflammatory markers [ 16 , 17 ], and lean body mass [ 13 , 14 , 16 , 18 ]. Conversely, 4 of the 7 studies reported negative effects on high-density lipoprotein (HDL) cholesterol [ 14 , 15 , 17 ], visceral adipose tissue (VAT) [ 15 ], increased insulin resistance, and increased risk of cardiovascular disease (CVD) [ 12 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, both estrogen + testosterone and estrogen + placebo groups showed a significant decline in plasma fibrinogen levels, indicating an estrogenic effect on the latter parameter, which was preserved in those treated with testosterone [ 16 ]. In addition, Kocoska-Maras et al [ 17 ] conducted a 48-week study using a combination of oral testosterone undecanoate (40 mg/day) and oral estradiol valerate (2 mg/day). Their findings suggest a modest influence on inflammatory markers with no apparent adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations